The relationship between organizational learning capability and job satisfaction of the employees of International Islamic University Malaysia (IIUM) - Jafari, Shokooh (Institute of Education, International Islamic University Malaysia, 2013)
The main purpose of this study is to explore the relationship between organizational learning capability (OLC) and job satisfaction at International Islamic University Malaysia (IIUM). Furthermore, it attempts to discover the level of organizational learning capability regarding the five dimensions of OLC namely; experimentation, risk taking, interaction with the external environment, dialogue and participative decision making that are currently practiced among employees. Finally, the study tries to discover the significant correlation of these five dimensions with job satisfaction. For these objectives, data were collected from eight faculties namely; Law, Education, Economics and Management Science, Architecture and Environmental Design, Engineering, Information and Communication Technology (ICT), Islamic Revealed Knowledge and Human Science (IRK), and Languages and Management. The respondent was non–academic staff. A questionnaire, using the Five-point Likert Scale, was applied as an instrument to collect data. The survey was addressed to 212 non-academic staff. For testing and analyzing the hypotheses and research questions, Pearson correlation coefficient, descriptive analysis and multiple regressions had been used. The results of study show that there is a positive relationship between organizational learning capabilities with job satisfaction. Furthermore, the results revealed the five dimensions of organizational learning capability (experimentation, risk taking, interaction with the external environment, dialogue and participative decision making) had positive relationship with job satisfaction. In addition, the analysis reveals a high level of organizational learning capability was practiced among non-academic staff. However, the regression analysis illustrates that two of dimensions of OLC namely risk taking and dialogue are not statistically significant on job satisfaction. Finally, the study provides some suggestions on how to improve and identify the factors of organizational learning capability and the effect of these on job satisfaction among staff.